A comparative study of parasitism in insects : why some Odonata species have parasites and others do not? - Ilvonen, Jaakko (fi=Turun yliopisto|en=University of Turku|, 2018)
Parasites are one of the most diverse groups of animals, capable of infecting virtually all other organisms on the planet. They are a strong evolutionary force, influencing genetic diversity and thereby affecting individuals, populations and entire species. Studies of host-parasite interactions have frequently examined how host individuals and their parasites interact, but this focus on the host individual offers a very narrow perspective on the general dynamics of hosts and their parasites. To understand the dynamics of hosts and their parasites on an evolutionary scale, examination has to be moved beyond the individual, to include multiple host species, multiple parasites, and various host species traits. To this end, I decided to expand our knowledge by studying the host-parasite interactions of a large number of damselfly and dragonfly species and their endoand ectoparasites. I evaluated specific physical, behavioral and distributional traits of the host species along with their parasitism in order to understand what traits affect parasitism. In addition, I examined these associations using the known evolutionary tree of the different damselfly and dragonfly hosts. Using this method I was able to get a deeper understanding on the co-evolution between damselflies, dragonflies and their endo- and ectoparasites. In paper I, I confirmed that there is huge variation in endo- and ectoparasitism between different damselfly and dragonfly species. I also found that damselfly females had more ectoparasites than males did, but there was no difference between sexes in dragonflies. In paper II, I found that there is significant variation between different damselfly and dragonfly species in their strength of immune response and body mass. Using the evolutionary tree of these host species I also discovered that closely related species are more similar in their parasitism and in their two evaluated traits than would be expected if the species were drawn at random. In paper III, I discovered that both endo- and ectoparasites tend to infect the same host species which are relative small, live in high density and are common. Paper IV continued my investigation and I found that territorial or large species have fewer ectoparasites than non-territorial or small species and I also found that northern species have more ectoparasites than southern ones. It seems that the larger size of damselfly and dragonfly species lowers their susceptibility to parasitism. However, whether this is the cause of the host’s physical traits or due to the infection mechanism and/or preference of the parasite, remains unknown. Further studies are required to understand how the size of the host influences other traits and subsequently co-evolution between damselflies, dragonflies and their endo- and ectoparasites.

Loiset ovat monimuotoinen eliöryhmä ja ne kykenevät hyödyntämään miltei kaikkia muita eliöitä. Loiset ovat vahva evoluutiota ohjaava voima, ja ne voivat vaikuttaa geneettiseen monimuotoisuuteen ja näin ollen myös yksilöihin, populaatioihin ja lajeihin. Loistutkimus on usein keskittynyt isäntäyksilön ja sen loisten välisen vuorovaikutuksen tutkimiseen, mutta tämä yksilöä korostava tutkimus antaa hyvin yksipuolisen ja kapean kuvan isäntien ja loisten välisestä vuorovaikutuksesta. Ymmärtääksemme isäntälajien ja loisten välistä vuorovaikutussuhdetta riittävän kattavasti, tulee tutkimuksissa käyttää suuria määriä isäntälajeja ja niiden loisia sekä mahdollisimman monia isäntälajin ja loisten ominaisuuksia. Lisätäkseni ymmärrystä tältä osa-alueelta, tutkin suuren määrän aito- ja hentosudenkorentolajeja ja vertailin niiden ulko- ja sisäloisten määriä. Tutkin näiden sudenkorentolajien fyysisiä, maantieteellisiä ja käyttäytymiseen pohjautuvia ominaisuuksia selvittääkseni, mitkä näistä ominaisuuksista vaikuttavat kyseisten isäntälajien sisä- ja ulkoloisten määrään. Yhdistämällä nämä vuorovaikutussuhteet uusimpaan tutkimustietoon sudenkorentojen sukupuusta, pyrin myös selvittämään, millä tavalla sudenkorentoisännät ja niiden loiset ovat kehittyneet yhdessä. Ensimmäisessä työssäni totesin, että eri sudenkorentolajien välillä on suuria eroja niin sisä- kuin ulkoloisten määrässä. Huomasin myös, että hentosudenkorentonaarailla on selvästi enemmän loisia kuin koirailla, mutta tätä sukupuolten välistä eroa ei löytynyt aitosudenkorennoilta. Toisessa työssäni löysin sudenkorentolajien väliltä selkeitä eroja niin immuunipuolustusvasteessa kuin ruumiin koossa. Hyödyntämällä sudenkorentojen sukupuuta havaitsin myös, että läheistä sukua olevat lajit ovat keskenään todennäköisemmin samanlaisia sekä sisä- ja ulkoloisinnan, että immuunivasteen ja koon osalta kuin sukupuusta otetut satunnaiset isäntälajit. Kolmannessa työssäni havaitsin, että niin sisä- kuin ulkoloisetkin tuntuvat hyödyntävän todennäköisimmin pieniä, tiheästi eläviä ja yleisiä sudenkorentolajeja. Viimeisessä työssäni kävi ilmi, että sisäloisia on pienemmällä todennäköisyydellä isoilla, reviirillisillä ja pohjoisemmilla sudenkorentolajeilla kuin pienillä, ei-reviirillisillä tai pohjoisemmilla lajeilla. Vaikuttaa siltä, että sudenkorentolajin suuri koko pienentää lajin todennäköisyyttä olla loisittu. Ei kuitenkaan vielä tiedetä, johtuuko tämä isäntälajin fyysisistä ominaisuuksista vai loisten tartuntatavasta ja/tai halusta valita tietty isäntälaji. Jatkotutkimuksia tarvitaan, jotta ymmärretään, miten isäntälajin koko vaikuttaa sen muihin ominaisuuksiin sekä sen yhteiskehitykseen loisten kanssa